Method for Calculating the Consistent Market Value of Appraisal Property - EGOROVA, Anastasia; ISLAMOVA, Guzal; KURYLEVA, Olga; LAVRENTYEVA, Larisa; SINEVA, Nadezhda; YASHKOVA, Elena (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The article deals with the author's methodology for the reconciliation of the market value of the property being appraised, based on the matrix of alignment of qualitative judgments of the appraiser and the representation of the values found in the form of normalized fuzzy numbers with a Gaussian membership function. The alignment of the market values of the appraisal property, obtained by methods of comparative, cost-based, and income-based approaches that are correctly applied by the appraiser, and the construction of a confidence interval is a very important problem in both theoretical and practical terms. In the research process, 11 assessment standards studied. The dialectical approach, methods of system analysis, expert estimates, statistical groupings, forecasting and modelling were used. The empirical base of the study was made up of information sources, materials on the assessment of the market value of appraised property, legislative acts, and other legal documents in the field under study. The authors provide an example of the calculation, illustrating the application of the estimated correlations obtained by him, and represent the results of the appraisal property's market value calculation for each approach as normalized fuzzy numbers with a Gaussian membership function.